Optimal monetary policy under administered prices - Kater, Guilherme de Oliveira (2015)
This work aims to analyze the interaction and the effects of administered prices in the economy, through a DSGE model and the derivation of optimal monetary policies. The model used is a standard New Keynesian DSGE model of a closed economy with two sectors companies. In the first sector, free prices, there is a continuum of firms, and in the second sector of administered prices, there is a single firm. In addition, the model has positive trend inflation in the steady state. The model results suggest that price movements in any sector will impact on both sectors, for two reasons. Firstly, the price dispersion causes productivity to be lower. As the dispersion of prices is a change in the relative price of any sector, relative to general prices in the economy, when a movement in the price of a sector is not followed by another, their relative weights will change, leading to an impact on productivity in both sectors. Second, the path followed by the administered price sector is considered in future inflation expectations, which is used by companies in the free sector to adjust its optimal price. When this path leads to an expectation of higher inflation, the free sector companies will choose a higher mark-up to accommodate this expectation, thus leading to higher inflation trend when there is imperfect competition in the free sector. Finally, the analysis of optimal policies proved inconclusive, certainly indicating that there is influence of the adjustment model of administered prices in the definition of optimal monetary policy, but a quantitative study is needed to define the degree of impact.